"A Different Kind of Activism": The University of Florida Committee on Sexism and Homophobia, 1981–1992. (August 2019) - Beck, Brittney L.
By 1982, the queer student group at the University of Florida (UF) had gained official recognition and space on campus. However, in 1987 they decided to remove themselves from university life. The group reemerged in 1991 with the assistance of a new, quietly radical entity—The UF Committee on Sexism and Homophobia. Anchored by the oral histories of Phyllis Meek and Irene Stevens, the founders of the UF Committee on Sexism and Homophobia, the historical analysis of this overlooked episode is designed to illuminate the quieter role faculty and staff in higher education played in sustaining the civil rights and human dignities of queer people at UF during a time when students activism had lost momentum.